CD39+PD-1+ regulatory T cells in melanoma: key drivers of systemic immunosuppression and prognostic biomarkers - Qiao, Guanlin; He, Hongxia; Wang, Xiaobing (Frontiers in Oncology, 2025)
Melanoma remains a major challenge in oncology because of its aggressive behavior and intricate immune interactions. Advances in immunophenotyping and single-cell atlas technologies have revealed heterogeneous regulatory T cell (Treg) subsets, among which peripheral blood CD39+PD-1+ Tregs have emerged as key mediators of systemic immunosuppression. This review summarizes current evidence on their immunoregulatory functions, emphasizing their role in suppressing anti-tumor immunity and contributing to poor clinical outcomes. By integrating immune atlas data with clinical observations, we outline the mechanisms by which this subset shapes both the tumor microenvironment and systemic immune responses. We further discuss their potential as prognostic biomarkers and therapeutic targets to optimize immunotherapy strategies. In addition, we highlight how this subset interacts with other immunosuppressive pathways, reinforcing resistance to immune checkpoint inhibitors. Despite these advances, challenges remain in fully characterizing this population and translating findings into clinical application. This review provides a comprehensive overview of the significance of CD39+PD-1+ Tregs in melanoma immunopathology and highlights future directions to advance precision immunotherapy and improve patient prognosis.